2017
DOI: 10.3928/00220124-20171115-06
|View full text |Cite
|
Sign up to set email alerts
|

Professor in Residence: An Innovative Academic-Practice Partnership

Abstract: This article describes an academic-practice partnership between an American Nurses Credentialing Center Magnet-designated hospital and an academic nurse educator that has increased the hospital's capacity for research, evidence-based practice, and support for nurses continuing their education. Through close collaboration with the full-time nurse researcher and members of the nursing education department, the professor in residence consults with clinical staff to support completion of research and evidence-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…6 Office of Medical Education, Faculty of Medicine, Herston Road, Herston, QLD 4005, Australia. 7 Menzies Health Institute, Griffith University, Gold Coast, QLD, Australia.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Office of Medical Education, Faculty of Medicine, Herston Road, Herston, QLD 4005, Australia. 7 Menzies Health Institute, Griffith University, Gold Coast, QLD, Australia.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…For example, Pager et al [4] found that AHPs are motivated to do research in order to develop skills, increase job satisfaction and address identified problems, while barriers to research engagement included lack of time, skills and having other work priorities. Emergent strategies addressing some of these barriers include increasing research skills and capability through specific education initiatives [5], collaboration with universities and employing research facilitators within the healthcare service to provide guidance and support [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of strategies for increasing the use of EBP by hospital‐based nurses have been described in the literature to date. U.S.‐based strategies include the following: Academic‐service partnerships in which nurse scientists from schools of nursing are embedded in academic hospital settings and participate in population‐specific EBP committees (e.g., perioperative; Duffy, Stroups, Culp, Lucke‐Wold, & Sand‐Jecklin, ) or work individually with direct care nurses or teams of nurses leading either EBP or research projects (Hinic, Kowalski, & Silverstein, ); EBP “nurse consultants” employed in community hospitals to advise and guide bedside nurses (Brockopp, Corley, Moe, & Schreiber, ); and clinical inquiry specialists, doctoral‐level nurse scholars who work with nurses in outpatient oncology centers (Boucher, Underhill, Roper, & Berry, ). Internationally, 10–14 weeks of academic EBP courses have been held in acute care settings (Wu, Brettle, Zhou, Ou, Wang, & Wang, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of a partnership between the academic and the clinical organizations has been highlighted in the literature. A close collaboration and a shared philosophy is beneficial for both the clinic and the university (Glazer et al, 2011;Hinic et al, 2017). A partnership also has the potential to close the gap between theory and practice (Huston et al, 2018).…”
Section: Discussionmentioning
confidence: 99%